2021
DOI: 10.33963/kp.a2021.0004
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale and left atrial appendage flow velocity predict atrial fibrillation recurrence post cryoballoon ablation

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
2
17
0
2
Order By: Relevance
“…The association between increased left atrial size and AF recurrence post-ablation has been welldocumented in previous studies [2]. In line with the findings of the study of Kiełbasa et al [1], reduced left atrial appendage velocity has been found to be associated with increased risk of AF after cardiac surgery [3]. In our view, the most intriguing finding of this study is the 79% increased risk of AF recurrence associated with the presence of a PFO.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…The association between increased left atrial size and AF recurrence post-ablation has been welldocumented in previous studies [2]. In line with the findings of the study of Kiełbasa et al [1], reduced left atrial appendage velocity has been found to be associated with increased risk of AF after cardiac surgery [3]. In our view, the most intriguing finding of this study is the 79% increased risk of AF recurrence associated with the presence of a PFO.…”
supporting
confidence: 89%
“…The study by Kiełbasa et al [1] provides additional evidence on the intriguing association between PFO and AF with a novel perspective that requires further testing in independent cohorts.…”
mentioning
confidence: 99%
See 3 more Smart Citations